La Juventud Uruguaya de Pie y su relación con la violencia política en la coyuntura previa el golpe de Estado (1970-1973) - Gabriel Bucheli (Centre de Recherches sur les Mondes Américains, 2016)
This work investigates the participation of the “Juventud Uruguaya de Pie” (JUP) in the scene of violence installed in Uruguay between 1970 and 1973. The JUP was a right-wing youth movement born in the heart of the conservative reaction resulting from the political polarization which the country transited from c. 1968. This movement represented the right-wing social subject in a symbolic space in the dispute with the left-wing: the youth camp. Its more visible action was centered in student action, by confronting the left-wing hegemony in those spaces. It has been installed as a “common sense” that the JUP was directly responsible for the violent actions of the right against the left militant. We propose to challenge this conjecture from a set of primary sources.